THE IMPACT OF WORK-LIFE BALANCE AND FLEXIBLE WORK ARRANGEMENTS ON BURNOUT AND TURNOVER INTENTIONS IN GENERATION Z WORKERS - Sujarwadi Sujarwadi; Helmi Azahari; Erna Kusumawati; Muhamad Risal Tawil; Adi Masliardi (Universitas Pahlawan Tuanku Tambusai, 2026)
The phenomenon of high burnout rates and turnover rates among Generation Z workers poses a strategic challenge for human resource management in the era of digital transformation. This study aims to analyze the effect of Work-Life Balance (WLB) and Flexible Work Arrangements (FWA) on burnout and its implications for turnover intentions among Generation Z workers. This study uses a quantitative approach with a causal explanatory design. Data were collected from 210 Generation Z worker respondents in the financial services and technology sectors through a structured questionnaire with a purposive sampling technique. Data analysis was conducted using the Structural Equation Modeling method based on Partial Least Squares (SEM-PLS) with the help of SmartPLS 4.0 software. The results showed that WLB and FWA had a negative and significant effect on burnout. Furthermore, burnout was proven to have a positive and significant effect on turnover intentions. Mediation analysis confirmed that burnout acts as a partial mediating variable in the relationship between WLB and FWA on turnover intentions. Simultaneously, flexibility and work-life balance policy interventions were able to significantly reduce emotional exhaustion and turnover intentions among Generation Z. The implications of this research emphasize the importance of designing adaptive work environments that respect personal life boundaries to foster the retention of young talent. Keywords: Work-Life Balance, Flexible Work Arrangements, Burnout, Turnover Intentions, Generation Z